The Arabidopsis E3 ubiquitin ligase DOA10A promotes localization of abscisic acid (ABA) receptors to the membrane through mono-ubiquitination in ABA signaling - Liu, Cuixia (The New phytologist, 2025)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.